Titanium-doped iron phosphate as well as preparation method and application thereof

By forming an interstitial solid solution of anatase titanium dioxide and iron phosphate in iron phosphate, the problem of reduced iron-phosphorus ratio caused by titanium doping is solved, and the capacity performance and electrochemical performance of titanium-doped iron phosphate are improved.

CN120622435APending Publication Date: 2025-09-12HUBEI HONGRUN HIGH-TECH NEW MATERIALS CO LTD
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202510805080.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-06-16
Publication Date
2025-09-12

AI Technical Summary

Technical Problem

In the existing preparation method of titanium-doped iron phosphate, titanium doping leads to a decrease in the iron-phosphorus ratio in the iron phosphate lattice, resulting in a decrease in capacity performance.

Method used

By mixing the iron source solution with the titanium source slurry that has been crystallized, co-precipitation of hydrated titanium dioxide and iron phosphate is achieved under the adjustment of phosphorus source solution and pH. After sintering, anatase titanium dioxide and iron phosphate interstitial solid solution is formed to avoid the replacement of iron element by titanium element.

Benefits of technology

The iron-phosphorus ratio of titanium-doped iron phosphate is increased, and the capacity performance and electrochemical performance of the battery are improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120622435A_ABST
    Figure CN120622435A_ABST
Patent Text Reader

Abstract

The invention provides titanium-doped iron phosphate and a preparation method and application thereof, and belongs to the technical field of battery materials.The preparation method of the titanium-doped iron phosphate comprises the steps that an iron source solution and titanium source slurry subjected to crystal transformation treatment are mixed to obtain first slurry; a phosphorus source solution and a pH regulator are sequentially added into the first slurry, and second slurry with the pH larger than 2 is obtained; filtering the second slurry to obtain a first filter cake, rinsing the first filter cake, and dispersing the first filter cake with a phosphoric acid solution to obtain a third slurry; after the third slurry is aged, the obtained aged slurry is filtered, washed, dried and sintered in sequence, and titanium-doped iron phosphate is obtained. The titanium source slurry subjected to crystal transformation treatment is introduced into an iron phosphate synthesis system, hydrated titanium dioxide in the sintered titanium source slurry is converted into anatase titanium dioxide, the anatase titanium dioxide and iron phosphate form an interstitial solid solution, and the prepared titanium-doped iron phosphate has a relatively high iron-phosphorus ratio, so that the capacity performance of a secondary battery is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of battery materials, and in particular to a titanium-doped iron phosphate and a preparation method and application thereof. Background Art

[0002] In modern society, secondary batteries provide power for various applications, such as new energy vehicles. Lithium-ion batteries, as the most widely used secondary battery, are particularly gaining attention. In the preparation of lithium-ion battery materials, performance is often improved by doping with small amounts of heterogeneous ions. For example, in the preparation of iron phosphate, doping with a small amount (50-5000 ppm) of titanium improves the rate performance of the resulting secondary battery and significantly reduces its impedance. Therefore, doping iron phosphate with titanium has become a hot topic among researchers.

[0003] Currently, the preparation method of titanium-doped iron phosphate generally uses a mixture of an iron source and a titanium source as the base liquid, then adds a phosphorus source to the base liquid for a co-precipitation reaction to obtain an iron phosphate slurry, and finally performs filter pressing, washing, and calcination to obtain anhydrous iron phosphate doped with titanium. However, the titanium-doped iron phosphate prepared by the existing technology is the product of the co-precipitation of titanium phosphate and iron phosphate. This will cause the titanium element to partially replace the iron element in the iron phosphate lattice, resulting in a decrease in the iron-phosphorus ratio as the titanium content increases. The electrical performance of iron phosphate material batteries is related to the valence state change of the iron element. A decrease in the proportion of iron element will reduce the capacity performance of the material.

[0004] Therefore, there is an urgent need to provide a preparation method of titanium-doped ferric phosphate to improve the capacity performance of existing titanium-doped ferric phosphate. Summary of the Invention

[0005] In view of the technical problems existing in the background technology, the present application provides a titanium-doped iron phosphate and its preparation method and application, aiming to solve the technical problem of low capacity performance of the existing titanium-doped iron phosphate due to the decrease in the iron-phosphorus ratio.

[0006] In a first aspect, the present invention provides a method for preparing titanium-doped ferric phosphate, comprising the following steps: Providing an iron source solution and a titanium source slurry that has undergone crystallization treatment; Mixing the iron source solution and the crystallized titanium source slurry to obtain a first slurry; adding a phosphorus source solution and a pH adjuster to the first slurry in sequence to obtain a second slurry having a pH value greater than 2; The second slurry is filtered to obtain a first filter cake, and the first filter cake is rinsed and dispersed in a phosphoric acid solution to obtain a third slurry; The third slurry is subjected to aging treatment to obtain aged slurry, and then the aged slurry is filtered, washed, dried and sintered in sequence to obtain titanium-doped ferric phosphate.

[0007] In the technical solution of the embodiment of the present application, the iron source solution is mixed with the titanium source slurry that has been crystallized, and co-precipitation of hydrated titanium dioxide and iron phosphate in the titanium source slurry is achieved under phosphorus source solution and certain pH conditions, thereby reducing the formation of titanium phosphate. After sintering treatment, the hydrated titanium dioxide forms anatase titanium dioxide, and forms an interstitial solid solution with iron phosphate. The titanium element doping mode is changed from the form of titanium ions replacing iron ion sites in the iron phosphate lattice to the form of anatase titanium dioxide and iron phosphate interstitial solid solution, thereby avoiding the problem of capacitance decrease caused by the decrease in the iron-phosphorus ratio in the iron phosphate material when the doped titanium content is high.

[0008] In some embodiments, the steps of preparing the crystallized titanium source slurry include: Stirring the titanium source solution at pH <1 and 105-115°C to obtain a titanium source slurry; wherein the concentration of the titanium source solution is 2-8 wt%; and / or, The stirring time of the stirring reaction is 30-60 min and the stirring frequency is 40-60 Hz; and / or, The titanium source is at least one of titanyl sulfate and titanium chloride.

[0009] In this embodiment, the titanium source solution is subjected to high temperature hydrolysis and crystallization treatment to convert (-Ti-O-) 2+ The titanium dioxide is converted into a stable hydrated titanium dioxide precipitate, which facilitates the formation of an interstitial solid solution with ferric phosphate during the subsequent sintering process. The particle size of the hydrated titanium dioxide can be controlled by controlling the appropriate titanium source concentration, the stirring intensity and stirring time of the crystal transformation treatment, thereby obtaining hydrated titanium dioxide with a certain particle size, which is convenient for improving its mixing degree with ferric phosphate.

[0010] In some embodiments, the D50 particle size of the solid phase particles in the titanium source slurry is 0.9-1.4 μm, and the D90 particle size is 1.4-2.1 μm.

[0011] In this embodiment, by controlling the particle size of hydrated titanium dioxide in the titanium source slurry within a suitable range, it is beneficial for the hydrated titanium dioxide to be evenly distributed in the iron source solution, so that after the iron source and the phosphorus source are mixed and reacted, a co-precipitation of hydrated titanium dioxide and iron phosphate is obtained, and after sintering, an interstitial solid solution of anatase titanium dioxide and iron phosphate is formed, thereby achieving uniform doping of the titanium element and improving the degree of doping.

[0012] In some embodiments, the molar ratio of iron in the iron source solution to titanium in the titanium source slurry is (10-90):1; and / or, The molar ratio of phosphorus in the phosphorus source solution to iron in the iron source solution is (0.95-1.05):1; and / or, The phosphorus source is at least one of sodium phosphate, ammonium phosphate, ammonium monohydrogen phosphate, ammonium dihydrogen phosphate, sodium dihydrogen phosphate, and potassium dihydrogen phosphate; and / or, The iron source is at least one of a soluble iron salt, a soluble ferrous salt, and ferric hydroxide.

[0013] In this embodiment, by controlling the molar ratio of iron to titanium to (10-90):1, a titanium-doped iron phosphate material with an appropriate titanium content is obtained. Excessive titanium content reduces the number of active lithium ions in the lithium iron phosphate cathode material prepared from the titanium-doped iron phosphate, thereby affecting the discharge capacity and electrochemical performance of the lithium iron phosphate. However, too little titanium content fails to effectively improve the rate capability, impedance, and other performance of the battery prepared from the titanium-doped iron phosphate. By controlling the molar ratio of phosphorus to iron to (0.95-1.05):1, a titanium-doped iron phosphate material with high capacitance is obtained. However, if the iron-to-phosphorus ratio is too low, the phosphorus content in the product is relatively high, failing to meet the technical specifications for battery-grade iron phosphate. However, if the iron-to-phosphorus ratio is too high, impurities such as iron oxide are generated. These impurities can hinder the diffusion of lithium ions in lithium-ion batteries prepared from the titanium-doped iron phosphate, reducing electrochemical performance.

[0014] In some embodiments, the step of aging the third slurry comprises: stirring the third slurry at 85-95° C. for 1-3 hours.

[0015] In this embodiment, the third slurry is subjected to an aging reaction under stirring conditions at 85-95° C., which can convert the ferric phosphate into ferric phosphate dihydrate crystals, thereby effectively removing impurities in the titanium-doped ferric phosphate and improving the purity of the titanium-doped ferric phosphate.

[0016] In some embodiments, in the sintering step, the sintering temperature is 600-800° C., and the sintering time is ≥2 h.

[0017] In this embodiment, by sintering at 600-800°C for more than 2 hours, hydrated titanium dioxide can be converted into anatase titanium dioxide, and dihydrated ferric phosphate can be converted into anhydrous ferric phosphate, thereby obtaining battery-grade titanium-doped ferric phosphate in the form of a solid solution of anatase titanium dioxide and anhydrous ferric phosphate, avoiding the problem of a decrease in the iron-phosphorus ratio due to titanium ion substitution in the iron phosphate lattice.

[0018] In a second aspect, an embodiment of the present application provides a titanium-doped ferric phosphate, which is prepared by the preparation method described in the first aspect.

[0019] In the technical solution of the embodiment of the present application, the titanium-doped ferric phosphate is prepared by the preparation method described in the first aspect, and thus has higher capacity performance.

[0020] In a third aspect, an embodiment of the present application provides a titanium-doped lithium iron phosphate positive electrode material, which is prepared from the titanium-doped iron phosphate described in the second aspect.

[0021] In the technical solution of the embodiment of the present application, the titanium-doped lithium iron phosphate positive electrode material is prepared from the titanium-doped lithium iron phosphate described in the second aspect, and thus has higher capacity performance.

[0022] In a fourth aspect, an embodiment of the present application provides a positive electrode plate, which includes the titanium-doped lithium iron phosphate positive electrode material described in the third aspect.

[0023] In the technical solution of the embodiment of the present application, the positive electrode plate includes the titanium-doped lithium iron phosphate positive electrode material described in the third aspect, and thus has higher capacity performance.

[0024] In a fifth aspect, an embodiment of the present application provides a secondary battery, which includes the positive electrode sheet described in the fourth aspect.

[0025] In the technical solution of the embodiment of the present application, the secondary battery includes the positive electrode plate described in the fourth aspect, and thus has better electrochemical performance.

[0026] The above description is only an overview of the technical solution of the present application. In order to more clearly understand the technical means of the present application, it can be implemented in accordance with the contents of the specification. In order to make the above and other purposes, features and advantages of the present application more obvious and easy to understand, the specific implementation methods of the present application are listed below. BRIEF DESCRIPTION OF THE DRAWINGS

[0027] To more clearly illustrate the technical solution of this application, the following is a brief introduction to the drawings used in this application. Obviously, the drawings described below are only some embodiments of this application. For those skilled in the art, other drawings can be derived from these drawings without inventive effort.

[0028] Figure 1 This is a flow chart of the preparation method of titanium-doped ferric phosphate in the examples of this application.

[0029] Figure 2 This is an SEM image of the titanium-doped iron phosphate prepared in Example 1 of the present application.

[0030] Figure 3 This is the SEM image of the titanium-doped ferric phosphate prepared in Comparative Example 1 of this application. DETAILED DESCRIPTION

[0031] The following embodiments of the technical solution of the present application will be described in detail with reference to the accompanying drawings. The following embodiments are only used to more clearly illustrate the technical solution of the present application and are therefore only examples and are not intended to limit the scope of protection of the present application.

[0032] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by those skilled in the art to which this application belongs; the terms used herein are only for the purpose of describing specific embodiments and are not intended to limit this application; the terms "including" and "having" and any variations thereof in the specification and claims of this application and the above-mentioned figure descriptions are intended to cover non-exclusive inclusions.

[0033] In the description of the embodiments of this application, the technical terms "first" and "second" are used only to distinguish different objects and should not be understood to indicate or imply relative importance or implicitly specify the quantity, specific order, or primary and secondary relationship of the indicated technical features. In the description of the embodiments of this application, the meaning of "plurality" is more than two, unless otherwise clearly and specifically defined.

[0034] References herein to "embodiments" mean that a particular feature, structure, or characteristic described in connection with the embodiments may be included in at least one embodiment of the present application. The appearance of this phrase in various places in the specification does not necessarily refer to the same embodiment, nor does it constitute an independent or alternative embodiment that is mutually exclusive of other embodiments. It is understood, both explicitly and implicitly, by those skilled in the art that the embodiments described herein may be combined with other embodiments.

[0035] In the description of the embodiments of this application, the term "and / or" is simply a description of the association relationship between associated objects, indicating that three relationships can exist. For example, A and / or B can represent the following three situations: A exists alone, A and B exist simultaneously, and B exists alone. In addition, the character " / " in this document generally indicates that the associated objects are in an "or" relationship.

[0036] In the description of the embodiments of the present application, the term "multiple" refers to more than two (including two). Similarly, "multiple groups" refers to more than two groups (including two groups), and "multiple pieces" refers to more than two pieces (including two pieces).

[0037] In the description of the embodiments of the present application, the technical terms "center", "longitudinal", "lateral", "length", "width", "thickness", "up", "down", "front", "back", "left", "right", "vertical", "horizontal", "top", "bottom", "inside", "outside", "clockwise", "counterclockwise", "axial", "radial", "circumferential", etc., indicating the orientation or position relationship, are based on the orientation or position relationship shown in the accompanying drawings, and are only for the convenience of describing the embodiments of the present application and simplifying the description, and do not indicate or imply that the device or element referred to must have a specific orientation, be constructed and operated in a specific orientation, and therefore cannot be understood as a limitation on the embodiments of the present application.

[0038] In the description of the embodiments of the present application, unless otherwise expressly specified or limited, technical terms such as "installed," "connected," "connected," and "fixed" should be understood in a broad sense. For example, they can refer to fixed connections, detachable connections, or integration; mechanical connections or electrical connections; direct connections or indirect connections through an intermediate medium; internal connections between two components or interactions between two components. Those skilled in the art can understand the specific meanings of the above terms in the embodiments of the present application based on specific circumstances.

[0039] In the prior art, the preparation method of titanium-doped iron phosphate materials usually uses a mixed solution of iron and titanium sources as the base liquid, then adds a phosphorus source to the base liquid for a co-precipitation reaction to obtain a slurry containing titanium phosphate and iron phosphate, and finally performs filter pressing, washing, and calcination to obtain anhydrous iron phosphate doped with titanium. However, the titanium-doped iron phosphate prepared by the prior art is the product of the co-precipitation of titanium phosphate and iron phosphate, which will cause titanium ions to be doped into the iron phosphate lattice to replace part of the iron element, resulting in a decrease in the iron-phosphorus ratio as the titanium content increases. The electrical performance of iron phosphate material batteries is related to the valence change of the iron element. A decrease in the proportion of iron elements will reduce the capacity performance of the material.

[0040] In order to solve the technical problem of low capacity performance of titanium-doped iron phosphate materials prepared by the prior art, the present application provides a titanium-doped iron phosphate and its preparation method and application, wherein the titanium source slurry that has been crystallized is mixed with the iron source solution as a base liquid, and then the co-precipitation of hydrated titanium dioxide and iron phosphate in the titanium source slurry is achieved under phosphorus source solution and certain pH conditions. After sintering, the hydrated titanium dioxide is converted into anatase titanium dioxide and forms an interstitial solid solution with iron phosphate. The obtained titanium-doped iron phosphate has a higher iron-phosphorus ratio, thereby obtaining a secondary battery with higher capacity.

[0041] In a first aspect, the present invention provides a method for preparing titanium-doped ferric phosphate, comprising the following steps: Providing an iron source solution and a titanium source slurry that has undergone crystallization treatment; Mixing the iron source solution and the crystallized titanium source slurry to obtain a first slurry; adding a phosphorus source solution and a pH adjuster to the first slurry in sequence to obtain a second slurry having a pH value greater than 2; The second slurry is filtered to obtain a first filter cake, and the first filter cake is rinsed and dispersed in a phosphoric acid solution to obtain a third slurry; The third slurry is subjected to aging treatment to obtain aged slurry, and then the aged slurry is filtered, washed, dried and sintered in sequence to obtain titanium-doped ferric phosphate.

[0042] In the technical solution of the embodiment of the present application, the iron source solution is mixed with the titanium source slurry that has been crystallized, and co-precipitation of hydrated titanium dioxide and iron phosphate in the titanium source slurry is achieved under phosphorus source solution and certain pH conditions. After sintering, the hydrated titanium dioxide is converted into anatase titanium dioxide, which reduces the formation of titanium phosphate and forms an interstitial solid solution with iron phosphate. The titanium doping mode is changed from the form of titanium ions replacing iron ion sites in the iron phosphate lattice to the form of anatase titanium dioxide and iron phosphate interstitial solid solution, avoiding the problem of capacitance decrease caused by the decrease in the iron-phosphorus ratio of the iron phosphate material when the doped titanium content is high.

[0043] Furthermore, in some embodiments, the steps of preparing the crystallized titanium source slurry include: Stirring the titanium source solution at pH <1 and 105-115°C to obtain a titanium source slurry; wherein the concentration of the titanium source solution is 2-8 wt%; and / or, The stirring time of the stirring reaction is 30-60 min and the stirring frequency is 40-60 Hz; and / or, The titanium source is at least one of titanyl sulfate and titanium chloride.

[0044] In the technical solution of the embodiment of the present application, the titanium source solution is subjected to high temperature hydrolysis and crystallization treatment to convert (-Ti-O-) 2+ The titanium dioxide is converted into a stable hydrated titanium dioxide precipitate, which facilitates the formation of an interstitial solid solution with ferric phosphate during the subsequent sintering process. The particle size of the hydrated titanium dioxide can be controlled by controlling the appropriate titanium source concentration, the stirring intensity and stirring time of the crystal transformation treatment, thereby obtaining hydrated titanium dioxide with a certain particle size, which is convenient for improving its mixing degree with ferric phosphate.

[0045] Furthermore, in some embodiments, the D50 particle size of the solid phase particles in the titanium source slurry is 0.9-1.4 μm, and the D90 particle size is 1.4-2.1 μm.

[0046] In the technical solution of the embodiment of the present application, by controlling the particle size of hydrated titanium dioxide in the titanium source slurry within an appropriate range, it is beneficial to uniformly distribute hydrated titanium dioxide in the iron source solution. After the iron source and the phosphorus source are mixed and reacted, a co-precipitation of hydrated titanium dioxide and iron phosphate is obtained, and then after sintering, an interstitial solid solution of anatase titanium dioxide and iron phosphate is formed, thereby achieving uniform doping of the titanium element and improving the degree of doping.

[0047] Furthermore, in some embodiments, the molar ratio of the iron element in the iron source solution to the titanium element in the titanium source slurry is (10-90):1; and / or, the molar ratio of the phosphorus element in the phosphorus source solution to the iron element in the iron source solution is (0.95-1.05):1; and / or, the phosphorus source is at least one of sodium phosphate, ammonium phosphate, ammonium monohydrogen phosphate, ammonium dihydrogen phosphate, sodium dihydrogen phosphate, and potassium dihydrogen phosphate; and / or, the iron source is at least one of a soluble iron salt, a soluble ferrous salt, and ferric hydroxide.

[0048] Specifically, the molar ratio of the iron element in the iron source solution to the titanium element in the titanium source slurry can be 10:1, 20:1, 40:1, 60:1, 80:1, 90:1, or any ratio within the aforementioned range. The molar ratio of the phosphorus element in the phosphorus source solution to the iron element in the iron source solution can be 0.95:1, 0.98:1, 1:1, 1.02:1, 1.05:1, or any ratio within the aforementioned range.

[0049] In the technical solution of the embodiment of the present application, by controlling the molar ratio of iron to titanium to (10-90):1, it is easy to obtain a titanium-doped iron phosphate material with an appropriate titanium content. If the titanium content is too high, the number of active lithium ions in the lithium iron phosphate positive electrode material made from the iron phosphate will be reduced, thereby affecting the electrochemical performance of the lithium iron phosphate. If the titanium content is too low, the rate performance, impedance, and other properties of the battery made from the iron phosphate cannot be effectively improved. By controlling the molar ratio of phosphorus to iron to (0.95-1.05):1, it is easy to obtain a titanium-doped iron phosphate material with high capacitance. If the iron-phosphorus ratio is too low, the phosphorus content in the product will be relatively high, failing to meet the technical specifications of battery-grade iron phosphate. If the iron-phosphorus ratio is too high, impurities such as iron oxide will be generated. These impurities will hinder the diffusion of lithium ions and reduce electrochemical performance.

[0050] Furthermore, in some embodiments, when the iron source is a soluble ferrous salt, when the phosphorus source solution and the pH adjuster are added to the first slurry in sequence, an oxidant is also added; wherein the oxidant is at least one of hydrogen peroxide, ozone, air, and oxygen; and the pH adjuster is at least one of sodium hydroxide and ammonia water.

[0051] In the technical solution of the embodiment of the present application, when the iron source is a soluble ferrous salt, the ferrous ions are oxidized into ferric ions by adding an oxidant, so as to facilitate the direct formation of iron phosphate precipitate during the coprecipitation process.

[0052] Furthermore, in some embodiments, the step of aging the third slurry includes: stirring the third slurry at 85-95° C. for 1-3 h.

[0053] In the technical solution of the embodiment of the present application, the third slurry is aged under stirring conditions at 85-95°C, which can convert iron phosphate into dihydrate iron phosphate crystals, thereby effectively removing impurities in titanium-doped iron phosphate and improving the purity of titanium-doped iron phosphate.

[0054] Furthermore, in some embodiments, in the sintering step, the sintering temperature is 600-800° C., and the sintering time is ≥2 h.

[0055] In the technical solution of the embodiment of the present application, by sintering at 600-800°C for more than 2 hours, hydrated titanium dioxide can be converted into anatase titanium dioxide, and dihydrated ferric phosphate can be converted into anhydrous ferric phosphate, thereby obtaining battery-grade titanium-doped ferric phosphate in the form of a solid solution of anatase titanium dioxide and anhydrous ferric phosphate, avoiding the problem of a decrease in the iron-phosphorus ratio due to titanium ion substitution in the iron phosphate lattice.

[0056] In a second aspect, an embodiment of the present application provides a titanium-doped ferric phosphate, which is prepared by the preparation method described in the first aspect.

[0057] In the technical solution of the embodiment of the present application, the titanium-doped ferric phosphate is prepared by the preparation method described in the first aspect, and thus has higher capacity performance.

[0058] In a third aspect, an embodiment of the present application provides a titanium-doped lithium iron phosphate positive electrode material, which is prepared from the titanium-doped iron phosphate described in the second aspect.

[0059] In the technical solution of the embodiment of the present application, the titanium-doped lithium iron phosphate positive electrode material is prepared from the titanium-doped lithium iron phosphate described in the second aspect, and thus has higher capacity performance.

[0060] In a fourth aspect, an embodiment of the present application provides a positive electrode plate, which includes the titanium-doped lithium iron phosphate positive electrode material described in the third aspect.

[0061] In the technical solution of the embodiment of the present application, the positive electrode plate includes the titanium-doped lithium iron phosphate positive electrode material described in the third aspect, and thus has higher capacity performance.

[0062] In a fifth aspect, an embodiment of the present application provides a secondary battery, which includes the positive electrode sheet described in the fourth aspect.

[0063] In the technical solution of the embodiment of the present application, the secondary battery includes the positive electrode plate described in the fourth aspect, and thus has better electrochemical performance.

[0064] Some specific examples are listed below. It should be noted that the examples described below are exemplary and are only used to explain the present application, and should not be construed as limiting the present application. Where specific techniques or conditions are not specified in the examples, the techniques or conditions described in the literature in this area or the product specifications are used. Reagents or instruments used without manufacturer's indication are all commercially available conventional products.

[0065] 1. Preparation method Example 1 (1) A titanium chloride solution with a concentration of 5 wt% was prepared and its pH was adjusted to <1. The solution was then stirred at 115 °C for 30 min with a stirring frequency of 60 Hz to obtain a titanium source slurry.

[0066] (2) A 2 mol / L ferric sulfate solution was prepared, and the titanium source slurry obtained in step (1) was added to the ferric sulfate solution, wherein the molar ratio of the iron element in the ferric sulfate solution to the titanium element in the titanium source slurry was 60:1. The mixture was evenly mixed to obtain a first slurry.

[0067] (3) Adding ammonium monohydrogen phosphate solution dropwise to the first slurry, and adding ammonia water to adjust the pH of the mixed system to >2, to obtain a second slurry containing hydrated titanium dioxide and iron phosphate; wherein the molar ratio of phosphorus in the ammonium monohydrogen phosphate solution to iron in the ferric sulfate solution is 1:1.

[0068] (4) The second slurry is filtered to obtain a first filter cake, and the first filter cake is rinsed with pure water to remove soluble impurities. The rinsed first filter cake is broken up and added into a dilute phosphoric acid solution to be evenly dispersed to obtain a third slurry.

[0069] (5) The third slurry was heated and stirred at 90°C for 3 h to convert the iron phosphate therein into iron phosphate dihydrate crystals to obtain an aged slurry.

[0070] (6) The aged slurry was filtered, washed with pure water, and dried in sequence, and sintered at 700 °C for 3 h to obtain titanium-doped iron phosphate.

[0071] Example 2 This embodiment provides a method for preparing titanium-doped ferric phosphate. Compared with Example 1, the difference is that in step (1): a titanium chloride solution with a concentration of 4 wt% is prepared and its pH is adjusted to <1, and then boiling and stirring at 115°C for 30 minutes with a stirring frequency of 60 Hz to obtain a titanium source slurry. The rest is roughly the same as Example 1 and will not be repeated here.

[0072] Example 3 This embodiment provides a method for preparing titanium-doped ferric phosphate. Compared with Example 1, the difference is that in step (1): a titanium chloride solution with a concentration of 6 wt% is prepared and its pH is adjusted to <1, and then boiling and stirring at 115°C for 30 minutes with a stirring frequency of 60 Hz to obtain a titanium source slurry. The rest is roughly the same as Example 1 and will not be repeated here.

[0073] Example 4 This embodiment provides a method for preparing titanium-doped ferric phosphate. Compared with Example 1, the difference is that in step (1): a titanium chloride solution with a concentration of 5 wt% is prepared and its pH is adjusted to <1, and then boiling and stirring at 115°C for 60 minutes with a stirring frequency of 60 Hz to obtain a titanium source slurry. The rest is roughly the same as Example 1 and will not be repeated here.

[0074] Example 5 This embodiment provides a method for preparing titanium-doped ferric phosphate. Compared with Example 1, the difference is that in step (1): a titanium chloride solution with a concentration of 5 wt% is prepared and its pH is adjusted to <1, and then boiling and stirring at 115°C for 30 minutes with a stirring frequency of 40 Hz to obtain a titanium source slurry. The rest is roughly the same as Example 1 and will not be repeated here.

[0075] Example 6 This embodiment provides a method for preparing titanium-doped ferric phosphate. Compared with Example 1, the difference is that in step (1): a titanium chloride solution with a concentration of 2 wt% is prepared and its pH is adjusted to <1, and then boiling and stirring at 115°C for 30 minutes with a stirring frequency of 60 Hz to obtain a titanium source slurry. The rest is roughly the same as Example 1 and will not be repeated here.

[0076] Example 7 This embodiment provides a method for preparing titanium-doped ferric phosphate. Compared with Example 1, the difference is that in step (1): a titanium chloride solution with a concentration of 8 wt% is prepared and its pH is adjusted to <1, and then boiling and stirring at 115°C for 30 minutes with a stirring frequency of 60 Hz to obtain a titanium source slurry. The rest is substantially the same as Example 1 and will not be repeated here.

[0077] Example 8 This embodiment provides a preparation method of titanium-doped ferric phosphate. Compared with Example 1, the difference is that in step (2): a ferric sulfate solution with a concentration of 2 mol / L is prepared, and the titanium source slurry obtained in step (1) is added to the ferric sulfate solution, wherein the molar ratio of the iron element in the ferric sulfate solution to the titanium element in the titanium source slurry is 20:1, and the first slurry is obtained after uniform mixing. The rest is substantially the same as Example 1 and will not be repeated here.

[0078] Example 9 This embodiment provides a preparation method of titanium-doped ferric phosphate. Compared with Example 1, the difference is that in step (2): a ferric sulfate solution with a concentration of 2 mol / L is prepared, and the titanium source slurry obtained in step (1) is added to the ferric sulfate solution, wherein the molar ratio of the iron element in the ferric sulfate solution to the titanium element in the titanium source slurry is 80:1, and the first slurry is obtained after uniform mixing. The rest is substantially the same as Example 1 and will not be repeated here.

[0079] Example 10 This embodiment provides a method for preparing titanium-doped ferric phosphate. Compared with Example 1, the difference is that in step (2): a ferric sulfate solution with a concentration of 2 mol / L is prepared, and the titanium source slurry obtained in step (1) is added to the ferric sulfate solution, wherein the molar ratio of the iron element in the ferric sulfate solution to the titanium element in the titanium source slurry is 10:1, and the first slurry is obtained after uniform mixing. The rest is substantially the same as Example 1 and will not be repeated here.

[0080] Example 11 This embodiment provides a method for preparing titanium-doped ferric phosphate. Compared with Example 1, the difference is that in step (2): a ferric sulfate solution with a concentration of 2 mol / L is prepared, and the titanium source slurry obtained in step (1) is added to the ferric sulfate solution, wherein the molar ratio of the iron element in the ferric sulfate solution to the titanium element in the titanium source slurry is 90:1, and the first slurry is obtained after uniform mixing. The rest is substantially the same as Example 1 and will not be repeated here.

[0081] Example 12 This embodiment provides a method for preparing titanium-doped ferric phosphate. Compared with Example 1, the difference is that in step (3): ammonium monohydrogen phosphate solution is added dropwise to the first slurry, and ammonia water is added to adjust the pH of the mixed system to >2, to obtain a second slurry containing hydrated titanium dioxide and ferric phosphate; wherein the molar ratio of phosphorus in the ammonium monohydrogen phosphate solution to iron in the ferric sulfate solution is 0.95:1. The other components are substantially the same as in Example 1 and are not described in detail here.

[0082] Example 13 This embodiment provides a method for preparing titanium-doped ferric phosphate. Compared with Example 1, the difference is that in step (3): ammonium monohydrogen phosphate solution is added dropwise to the first slurry, and ammonia water is added to adjust the pH of the mixed system to >2, to obtain a second slurry containing hydrated titanium dioxide and ferric phosphate; wherein the molar ratio of phosphorus in the ammonium monohydrogen phosphate solution to iron in the ferric sulfate solution is 1.05:1. The other components are substantially the same as in Example 1 and are not described in detail here.

[0083] Comparative Example 1 (1) Prepare a 5 wt% titanium chloride solution.

[0084] (2) A 2 mol / L ferric sulfate solution was prepared, and the titanium chloride solution of step (1) was added to the ferric sulfate solution, wherein the molar ratio of the iron element in the ferric sulfate solution to the titanium element in the titanium chloride solution was 60:1. The mixture was evenly mixed to obtain a first slurry.

[0085] (3) adding ammonium monohydrogen phosphate solution dropwise to the first slurry, and adding ammonia water to adjust the pH of the mixed system to be greater than 2, thereby obtaining a second slurry containing titanium phosphate and iron phosphate; wherein the molar ratio of phosphorus in the ammonium monohydrogen phosphate solution to iron in the ferric sulfate solution is 1:1.

[0086] (4) The second slurry is filtered to obtain a first filter cake, and the first filter cake is rinsed with pure water to remove soluble impurities. The rinsed first filter cake is broken up and added into a dilute phosphoric acid solution to be evenly dispersed to obtain a third slurry.

[0087] (5) The third slurry was heated and stirred at 90°C for 3 h to convert the iron phosphate therein into iron phosphate dihydrate crystals to obtain an aged slurry.

[0088] (6) The aged slurry was filtered, washed with pure water, and dried in sequence, and sintered at 700 °C for 3 h to obtain titanium-doped iron phosphate.

[0089] 2. Test Method (1) The titanium-doped iron phosphate prepared in Example 1 and Comparative Example 1 was characterized using a scanning electron microscope, and the titanium-doped iron phosphate prepared in Example 1 and Comparative Example 1 were obtained. Figure 2 and Figure 3 SEM images shown.

[0090] (2) The particle size of the hydrated titanium dioxide in the titanium source slurries obtained in the examples and comparative examples was measured by DLS. The results are shown in Table 1.

[0091] (3) The Fe content, P content and Fe / P molar ratio of the titanium-doped iron phosphate prepared in Examples 1-13 and Comparative Example 1 were measured in accordance with the national standard "GBT 30835-2014 Carbon-composite lithium iron phosphate positive electrode material for lithium-ion batteries". The results are shown in Table 2.

[0092] (4) The titanium content of the titanium-doped ferric phosphate products obtained in Examples 1-13 and Comparative Example 1 was measured using an inductively coupled plasma spectrometer. The results are shown in Table 2.

[0093] (5) The titanium-doped iron phosphates prepared in Examples 1 to 13 and Comparative Example 1 were used to prepare lithium-ion batteries. The prepared lithium-ion batteries were subjected to charge and discharge tests at current densities of 0.1 C and 1 C, respectively. The test results are shown in Table 3.

[0094] The preparation method of the lithium-ion battery is specifically as follows: (1) Preparation of positive electrode sheet: Using titanium-doped iron phosphate as a precursor, titanium-doped iron phosphate, deionized water, lithium carbonate and glucose are prepared into a mixture, and the mixture is sand-milled to a particle size of 350nm. The sand-milled slurry is spray-dried, and then the material is sintered at 720℃ in a nitrogen atmosphere for 20h to obtain titanium-doped lithium iron phosphate positive electrode material. The titanium-doped lithium iron phosphate positive electrode material is mixed with conductive carbon black and PVDF binder in a mass ratio of 90:5:5, and coated on a 12μm thick aluminum foil. The electrode sheet is then placed in an oven at 110℃ and dried for 12h. The dried electrode sheet is punched into 15mm diameter positive electrode discs.

[0095] (2) Preparation of lithium-ion batteries: The positive electrode disc was pressed with a compact density of 1.8 g / cm2, and a lithium sheet with a diameter of 16 mm was used as the counter electrode. The electrolyte was 1 M LiPF6 dissolved in EC:EMC:DEC with a volume ratio of 1:1:1. The battery was assembled in an LG2400 / 1000TS glove box produced by Weige Gas Purification Technology (Suzhou) Co., Ltd. to obtain a button half-cell.

[0096] 3. Analysis of test results of various embodiments and comparative examples Table 1

[0097] Table 2

[0098] Table 3

[0099] As can be seen from the data in Table 1, both the concentration of the titanium salt and the stirring intensity affect the particle size of the hydrated titanium dioxide in the titanium source slurry obtained after the crystallization treatment. Specifically, the data from Examples 1-3 and Examples 6-7 show that the particle size of the hydrated titanium dioxide in the titanium source slurry increases with increasing titanium salt concentration; the data from Examples 1 and 4 show that the stirring time has little effect on the particle size of the hydrated titanium dioxide formed; and the data from Examples 1 and 5 show that the particle size of the hydrated titanium dioxide in the titanium source slurry decreases with increasing stirring intensity.

[0100] As can be seen from the data in Tables 2 to 3, the iron-phosphorus ratio of the titanium-doped ferric phosphate prepared by the method of the present invention is greater than 0.96, and has a high charge and discharge capacity. As can be seen from the data in Examples 1 to 7, after the titanium source solution is subjected to crystallization treatment under different process conditions, the iron-phosphorus ratio of the final titanium-doped ferric phosphate obtained is not greatly affected, and thus the charge and discharge capacity of the lithium ion battery prepared therefrom is not significantly affected. As can be seen from the data in Examples 1 and 8 to 11, the molar ratio of the iron element in the iron source solution to the titanium element in the titanium source solution affects the content of the titanium element in the prepared titanium-doped ferric phosphate. As the amount of titanium element added increases, the content of titanium element in the titanium-doped ferric phosphate gradually increases, but its iron-phosphorus ratio remains basically unchanged. As the titanium element content in the titanium-doped ferric phosphate increases, the charge capacity of the lithium ion battery prepared therefrom shows a downward trend. The discharge capacity at 0.1C first remains basically unchanged and then decreases, and the discharge capacity at 1C shows a downward trend. From the data of Examples 1 and 12 to 13, it can be seen that the molar ratio of phosphorus in the phosphorus source solution and iron in the iron source solution affects the iron-phosphorus ratio of the prepared titanium-doped iron phosphate. As the amount of iron added increases, the iron-phosphorus ratio of the titanium-doped iron phosphate gradually increases, and the charge and discharge capacity of the lithium-ion battery prepared therefrom shows an increasing trend.

[0101] Furthermore, compared with Example 1, in Comparative Example 1, the titanium salt was not subjected to crystal transformation treatment. Therefore, the obtained titanium-doped iron phosphate was lattice-doped, that is, titanium ions replaced the iron ion positions in the iron phosphate lattice, resulting in a decrease in the iron-phosphorus ratio of the prepared titanium-doped iron phosphate, thereby reducing the charge and discharge capacity of the lithium-ion battery prepared using the titanium-doped iron phosphate, especially the charge and discharge capacity at a low rate of 0.1C.

[0102] Figure 2-3 The SEM images of the titanium-doped ferric phosphate prepared in Example 1 and Comparative Example 1 respectively show that the titanium-doped ferric phosphate prepared by the method of the present invention is an interstitial solid solution with uniform morphology formed by nano-scale ferric phosphate and micron-scale titanium dioxide, while the titanium-doped ferric phosphate prepared in Comparative Example 1 is a nano-scale ferric phosphate morphology, which belongs to lattice doping.

[0103] It should be noted that the present application is not limited to the above-mentioned embodiments. The above-mentioned embodiments are merely examples, and any embodiments having substantially the same structure and effect as the technical concept within the scope of the present application are all included in the technical scope of the present application. In addition, without departing from the scope of the present application, any other embodiments that can be conceived by those skilled in the art and that combine some of the constituent elements in the embodiments are also included in the scope of the present application.

Claims

1. A method for preparing titanium-doped ferric phosphate, characterized in that: The following steps are involved: Providing an iron source solution and a titanium source slurry that has undergone crystallization treatment; Mixing the iron source solution and the crystallized titanium source slurry to obtain a first slurry; adding a phosphorus source solution and a pH adjuster to the first slurry in sequence to obtain a second slurry having a pH value greater than 2; filtering the second slurry to obtain a first filter cake, and rinsing the first filter cake and dispersing it with a phosphoric acid solution to obtain a third slurry; The third slurry is subjected to an aging treatment to obtain an aged slurry, and then the aged slurry is filtered, washed, dried and sintered in sequence to obtain titanium-doped ferric phosphate.

2. The method for preparing titanium-doped ferric phosphate according to claim 1, wherein: The steps for preparing the titanium source slurry after crystallization treatment include: The titanium source solution is stirred and reacted at pH < 1 and 105-115°C to obtain a titanium source slurry; wherein, The concentration of the titanium source solution is 2-8 wt%; and / or, The stirring reaction has a stirring time of 30-60 min and a stirring frequency of 40-60 Hz; and / or, The titanium source is at least one of titanyl sulfate and titanium chloride.

3. The method for preparing titanium-doped ferric phosphate according to claim 1, wherein: The D50 particle size of the solid phase particles in the titanium source slurry is 0.9-1.4 μm, and the D90 particle size is 1.4-2.1 μm.

4. The method for preparing titanium-doped ferric phosphate according to claim 1, wherein: The molar ratio of the iron element in the iron source solution to the titanium element in the titanium source slurry is (10-90):1; and / or, The molar ratio of phosphorus in the phosphorus source solution to iron in the iron source solution is (0.95-1.05):1; and / or, The phosphorus source is at least one of sodium phosphate, ammonium phosphate, ammonium monohydrogen phosphate, ammonium dihydrogen phosphate, sodium dihydrogen phosphate, and potassium dihydrogen phosphate; and / or The iron source is at least one of a soluble iron salt, a soluble ferrous salt, and ferric hydroxide.

5. The method for preparing titanium-doped ferric phosphate according to claim 1, wherein: The step of aging the third slurry includes stirring the third slurry at 85-95° C. for 1-3 hours.

6. The method for preparing titanium-doped ferric phosphate according to claim 1, characterized in that: In the sintering step, the sintering temperature is 600-800° C., and the sintering time is ≥2 h.

7. A titanium-doped iron phosphate, characterized in that: The compound is prepared by the preparation method according to any one of claims 1 to 6.

8. A titanium-doped lithium iron phosphate positive electrode material, characterized in that: It is prepared from the titanium-doped ferric phosphate according to claim 7.

9. A positive electrode plate, characterized in that: It includes the titanium-doped lithium iron phosphate positive electrode material according to claim 8.

10. A secondary battery, characterized in that: Including the positive electrode sheet according to claim 9.

Citation Information

Patent Citations

  • Preparation method of spherical titanium-doped high-compaction lithium iron phosphate positive electrode material

    CN115676798A

  • Method for preparing high-performance lithium iron phosphate through segmented sintering

    CN115959644A

  • Method for preparing titanium-doped lithium iron phosphate by taking synthetic rutile mother liquor as raw material

    CN116692815A

  • Preparation process of titanium growth coated iron phosphate material

    CN117985671A

  • Preparation method and application of titanium-doped lithium iron phosphate positive electrode

    CN122291481A